The effect of screw spacing to the stiffness of profiled steel sheeting dry board (PSSDB) floor panel - Haslindah, Jaafar (2014)
Industrialized Building System (IBS) is one of the systems that has been widely used in construction, industry in Malaysia. One form of the IBS structure is Profiled Steel Sheeting Dry Board (PSSDB). PSSDB is a lightweight composite structure that comprises of Profile Steel Sheeting (PSS) and Dry Board (DB) which are connected by self-drilling and self-tapping screws. The objectives of this thesis are to determine the effect of screws spacing to the stiffness of profiled steel sheeting dry board and to investigate the relationship between the spacing of the screws and the stiffness of the panel. The testing was carried out by using 0.8 mm of Peva 45 and 9 mm thickness of Primaflex Board. The size of each specimen is 2440mm of length and 1200mm of width. Both of PSS and DB are connected by the screw with the spacing of 100mm, 200mm and 300mm. The bending test was performed to determine the maximum load that can supported by this PSSDB floor system before its failure. From the experiment, the maximum load can be applied on the panel with spacing 100 mm is 12.725 kN/m, for 200 mm is 9.807 kN/m, and for 300 mm is 9.184 kN/m. The deflection of each panels is 66.655 mm, 58.315 mm and 53.670 mm respectively. After calculating using the deflection formula, the stiffness of the panels is 92.084 kNm2/m, 85.208 kNm2/m, and 76.595 kNm2/m respectively with the spacing. From the result, it is concluded that the screw spacing can affect the stiffness of PSSDB panel. The shorter the distance between the screws, the stiffer panel will be. Therefore, the screws spacing plays an important role in determining the stiffness and the performance of the PSSDB panel.